Aplikasi Aplikasi Navigasi Visual Digital Menggunakan Realitas Tertambah Berbasis Android - Ronny Juwono (Computer Based Information System Journal, 2019)
Augmented Reality (AR) used in online business not merely to give new perspective of customer experience to product. AR is also used in operational such as in logistic to deliver product to the customer. The online map service such as Google Map, sometime fails to bring real visualization to user, especially when they are in unfamiliar places. AR may provide visualization of certain location’s coordinate. This digital visual navigation will help the user to choose which direction they should go, especially when Google Maps do not give accurate information related to the user’s surrounding. This papper provide solution to create Android application that can generate Augmented Reality navigation while user is using Google Map to travel. This papper is aimed to support the navigation for logistic management system especially for online business companies. In spite of the result of this reasearch, some findings and issues need to be discussed in the future. There was delay to generate the AR objects especially when user moves the device around fast. A simple 2D AR object is suggested for future work in order to decrease the delay.